Monitoring of Land Surface Change in Padang City Using Dinsar Sentinel-1a Method - Desi Syafriani; Saiyidinal Fikri; Quinoza Guvil (Journal of Applied Geospatial Information, 2022)
Padang City is the capital city of West Sumatra Province which is located on the west coast of the island of Sumatra which is generally associated with tectonic earthquakes. This condition causes the city of Padang to become a disaster-prone area, one of which is land surface changes. The earthquake that occurred caused shocks to the rock and soil layers, causing water below the earth's surface to come out and resulting in changes to the soil surface. Besides, changes in soil surface are also caused by several things, including excessive groundwater extraction and soil type factors. To reduce the bad impacts, it is necessary to monitor the ground surface and to reduce the risk of a disaster. In a broad scope, the use of SAR imagery using the DinSAR method can monitor changes in the land surface in the city of Padang. The data used were Sentinel -1A imagery based on 3 earthquakes with a strength of more than 5 magnitudes centered on the Mentawai Islands, on September 8, 19, and 21 October 2020. From this research, the results obtained from the earthquake 8 September 2020 with satellite recording data 28 August (slave) and September 9, 2020 (master), there was land subsidence with a range of 0 - 25 mm along the coast of Padang City. The 19 and 21 October 2020 earthquakes with satellite recording data of 27 October 2020 (slave) and 15 October 2020 (master) obtained almost even surface subsidence with a range of 0 - 40 mm throughout the residential area of ​​Padang City.